Solid-state battery and positive electrode and device thereof
By using a metal organic frame material containing carbonyl group as the positive electrode active material in solid-state lithium-ion batteries, the problems of low electronic conductivity and poor cycle performance of the positive electrode materials in the prior art are solved, and good rate performance and cycle stability are achieved.
Patent Information
- Application Number
- CN202410147927.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-31
- Publication Date
- 2025-04-15
AI Technical Summary
The positive electrode materials of existing solid-state lithium-ion batteries have low electronic conductivity and poor circulation performance, which limits the battery's rate performance and cycle stability.
A specific metal organic frame material is used as the positive electrode active material, and the organic ligand of the material comprises at least one carbon ring with 4-6 carbon atoms, and at least one carbon ring is embedded in the at least one carbon group.
It improves the rate performance and cycle stability of solid-state batteries, enhances electronic conductivity and structural stability, and improves specific capacity.
Smart Images

Figure CN119833575A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solid-state batteries, and in particular to a solid-state battery and a positive electrode and a device thereof. Background Art
[0002] Commercial lithium-ion batteries generally use liquid electrolytes, which have high safety risks such as flammability and explosion, limiting the widespread application of lithium-ion batteries. However, the safety of solid-state lithium-ion batteries using non-volatile and non-flammable solid electrolytes can be effectively improved.
[0003] At present, the commonly used positive electrode material in solid-state lithium-ion batteries is lithium iron phosphate, which has good cycle stability and low price, but has low electronic conductivity and poor cycle performance. Therefore, it is necessary to provide a positive electrode material for solid-state lithium batteries that can take into account both good electronic conductivity and structural stability, so that the solid-state battery has good rate performance and cycle stability. Summary of the invention
[0004] In view of this, the present application provides a solid-state battery and a positive electrode and a device thereof. The positive electrode uses a specific metal organic framework material as the positive electrode active material, so that the solid-state battery using the positive electrode can have good rate performance and cycle stability.
[0005] Specifically, the first aspect of the present application provides a positive electrode for a solid-state battery, the positive electrode comprising a positive electrode current collector and a positive electrode material layer arranged on at least one side surface of the positive electrode current collector, the positive electrode material layer comprising a positive electrode active material, the positive electrode active material comprising a metal-organic framework material, wherein the organic ligand of the metal-organic framework material comprises at least one carbon ring having 4-6 carbon atoms, and at least one of the carbon rings has at least one carbonyl group embedded therein.
[0006] The present application adopts a metal organic framework material as the positive electrode active material of a solid-state battery, and controls the material to select specific organic ligands containing at least one carbonyl group. These ligands can make the metal organic framework material have good electronic conductivity, structural stability and high specific capacity, so that the battery made using the positive electrode can have good rate performance, high cycle stability and high specific capacity.
[0007] The second aspect of the present application provides a solid-state battery, which includes the positive electrode described in the first aspect of the present application, a metal negative electrode, and a solid electrolyte membrane located between the positive electrode and the metal negative electrode.
[0008] The solid-state battery adopts the above-mentioned positive electrode of the embodiment of the present application. The solid-state battery has good rate performance, good cycle performance, high safety, and high discharge / charge specific capacity.
[0009] A third aspect of the present application provides a device comprising the solid-state battery described in the second aspect of the present application, wherein the device comprises an electrical device or an energy storage system. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 A schematic structural diagram of a positive electrode for a solid-state battery provided in an embodiment of the present application.
[0011] Figure 2 A schematic diagram of the structure of a solid-state battery provided in an embodiment of the present application. DETAILED DESCRIPTION
[0012] See also Figure 1 , Figure 1 A schematic diagram of the structure of a positive electrode 10 for a solid-state battery provided in an embodiment of the present application. The positive electrode 10 includes a positive electrode current collector 101 and a positive electrode material layer 102 ( Figure 1 In the figure, an example is given in which both sides of the positive electrode current collector 101 are provided with positive electrode material layers 102, the positive electrode material layer 102 includes positive electrode active materials, and the positive electrode active materials include metal-organic framework materials (Metal-Organic Frameworks, MOFs for short), wherein the organic ligands of the metal-organic framework materials include at least one carbon ring with 4-6 carbon atoms, and at least one of the carbon rings has at least one carbonyl group embedded therein.
[0013] Metal-organic framework materials are a type of porous crystalline materials with a periodic network structure formed by inorganic metal centers (metal ions or metal clusters) and organic ligands through coordination bonds or intermolecular forces. They can also be called "porous coordination polymers". Metal-organic framework materials have attracted much attention in the fields of gas storage and separation, catalysis, and sensing due to their easy-to-control structure and composition, high porosity, and large specific surface area. In recent years, metal-organic framework materials have also begun to be used in the field of batteries, but they are mainly used as electrolyte materials for solid-state batteries or modified materials for battery negative electrodes, and are rarely used in battery positive electrodes, especially directly as positive electrode active materials for battery positive electrodes.
[0014] The present application adopts metal organic framework materials as the positive electrode active materials of the positive electrode of the solid-state battery. Its high specific surface area and porous characteristics can absorb more carriers (such as lithium ions), and the molecular structure of the organic ligand of the metal organic framework material is controlled to contain at least one carbonyl -C (=O), which can effectively hybridize with the central metal ion, so that the electrons exist in the metal organic framework material in a delocalized state, increasing the electronic conductivity and structural stability of the metal organic framework material, and then when it is used as a positive electrode active material for the battery, it can reduce the positive electrode impedance, improve the battery's rate performance, and improve the battery's cycle stability. In addition, the above-mentioned metal organic framework material not only has a porous structure for the active ions (for lithium-ion batteries, the active ions are Li + ) is embedded / released therein, and the ligand of the metal organic framework material also has redox activity, and its electrochemically active components can bind to battery active ions (such as lithium ions) to increase the energy storage sites of the metal organic framework material, thereby making the specific capacity of the metal organic framework material higher. Therefore, the solid-state battery using the above positive electrode 10 can have a higher specific capacity, good rate performance and cycle stability.
[0015] In an embodiment of the present application, the organic ligand includes at least one carbon ring having 4-6 carbon atoms, and at least one of the carbon rings is embedded with at least one carbonyl group. That is, the carbon atom of the carbonyl group is one of the carbon atoms constituting the carbon ring. The organic ligand may be a cyclic ketone. It is understood that in the present application, carbonyl (-COOH) and aldehyde (-CHO) are not considered to contain carbonyl groups. Among them, the carbon ring may be an aliphatic ring or an aromatic ring. Among them, the six-membered aromatic ring is more conducive to the improvement of the conductivity of the above-mentioned metal organic framework material, thereby facilitating the improvement of the rate performance and cycle performance of the solid-state battery.
[0016] In the embodiment of the present application, the organic ligand contains 1 to 4 carbonyl groups in total. When the number of carbonyl groups is greater than or equal to 2, these carbonyl groups can be connected to the same carbon ring or to different carbon rings.
[0017] In some embodiments of the present application, the organic ligand includes one or more of the following compounds:
[0018]
[0019] Among them, the above-mentioned compound 1 can be called 4-hydroxycyclobut-2-enone. Compound 2 can be called 3-hydroxy-cyclobut-2-enone. Compound 3 can be called cyclobutane-1,3-dione. Compound 4 can be called cyclobut-3-ene-1,2-dione. Compound 5 can be called 3,4-dihydroxy-cyclobut-3-ene-1,2-dione. Compound 6 can be cyclobutane-1,2,3,4-tetraone. Compound 7 can be called cyclopenta-2,4-dienone. Compound 8 can be called cyclopenta-4-ene-1,2-dione. Compound 9 can be called 1,4-benzoquinone. Compound 10 can be called 2,5-dihydroxy-1,4-benzoquinone. Compound 11 can be called 1,4,5,8-tetrahydroxy-4a,9a-dihydroanthraquinone. Compound 12 can be called pyrene-4,5,9,10-tetraone.
[0020] Among them, in compounds 9 to 12, the carbonyl group is located on the six-membered aromatic ring. These compounds may have conjugated large π bonds in their structures. The metal organic framework materials made from them have excellent conductivity, which is more conducive to improving battery rate performance and cycle stability.
[0021] In some embodiments of the present application, the central metal ion of the metal organic framework material is a variable valence transition metal ion. Among them, the variable valence transition metal ion may include one or more of copper ions, iron ions, manganese ions, etc. These variable valence metal ions have a strong coordination effect with the above-mentioned organic ligands, and the structure of the resulting metal organic framework material is more stable; and these variable valence metal ions can provide abundant energy storage sites, and can participate in the redox process through conversion reactions or alloying reactions, thereby improving the specific capacity of the above-mentioned metal organic framework material. For example, copper ions can form lithium-copper alloys with lithium elements, and iron ions can form lithium-iron alloys with lithium elements.
[0022] The metal organic framework material can be formed by diffusion of organic ligands and metal ion sources at room temperature, or by solvent thermal reaction. The metal organic framework material is easy to synthesize and has strong structural stability.
[0023] In some embodiments of the present application, in the metal organic framework material, the molar ratio of the organic ligand to the central metal ion of the metal organic framework material is in the range of (0.5-2):1.
[0024] In the embodiment of the present application, the positive electrode material layer 102 also includes a binder and a conductive agent. Wherein, the binder and the conductive agent can be conventional choices in the field of batteries. Wherein, the binder may include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyimide (PI), polyacrylonitrile (PAN), polyacrylic acid (PAA), polyacrylate, styrene-butadiene rubber (SBR, also known as styrene-butadiene rubber), one or more of carboxymethyl cellulose, but not limited thereto. Wherein, the conductive agent may include conductive carbon black (such as Super-P, acetylene black, Ketjen black, 350G carbon black, etc.), graphite (such as artificial graphite KS-6), carbon nanotubes (referred to as CNT), graphene, etc. One or more, but not limited thereto.
[0025] In the embodiment of the present application, in the positive electrode material layer 102, the mass percentage of the binder or the conductive agent is independently within the range of less than or equal to 10%, for example, ≤8%, ≤5%, ≤3%, etc. Further, in the positive electrode material layer 102, the mass percentage of the binder or the conductive agent is independently greater than or equal to 0.1%, for example, ≥0.5%, ≥0.8%, or ≥1%, etc. The binder can improve the bonding force between the positive electrode active material particles, between the conductive agent particles, and between the positive electrode active material and the conductive agent. The appropriate amount of binder can ensure that the structural stability of the positive electrode material layer 102 is high, and helps the positive electrode material layer 102 to be stably attached to the positive electrode current collector 101, thereby facilitating the long cycle performance of the battery using the positive electrode 10. The presence of an appropriate amount of conductive agent helps to improve the overall electronic conductivity of the positive electrode material layer 102, thereby reducing the impedance of the positive electrode 10.
[0026] In some embodiments, the positive electrode material layer 102 includes the following percentages of components: 80%-99% of positive electrode active material, 0.5%-10% of binder, and 0.5%-10% of conductive agent. The components of the positive electrode material layer 102 have an appropriate ratio, so that the positive electrode material layer 102 can provide a higher reversible capacity and has good structural stability and low impedance. Specifically, the mass percentage of the binder or the conductive agent can be independently 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 4.5%, 5%, 6%, 7%, 8% or 9%, etc. The mass percentage of the positive electrode active material can be independently 82%, 85%, 88%, 90%, 92%, 95%, 98%, etc.
[0027] In some embodiments of the present application, the positive electrode active material in the positive electrode material layer 102 may include other types of positive electrode active materials in addition to the above metal organic framework materials.
[0028] In the embodiment of the present application, the mass percentage of the metal organic framework material in the positive electrode material layer 102 is greater than or equal to 80% and less than or equal to 99%. This ensures that the positive electrode material layer 102 contains enough of the above metal organic framework material as a positive electrode active material, so that the positive electrode material layer 102 provides a higher reversible capacity and better rate performance. Exemplarily, the mass percentage of the metal organic framework material in the positive electrode material layer 102 can be ≥83%, ≥85%, ≥88%, ≥90%, ≥92%, ≥94%, ≥95%, ≥96%, or ≥98%, etc.
[0029] In the present application, the preparation method of the positive electrode 10 is as follows: provide a metal organic framework material that meets the above requirements, mix the metal organic framework material with a binder and a conductive agent in an organic solvent in a certain proportion to obtain a positive electrode slurry; apply the positive electrode slurry on at least one side of the positive electrode current collector 101, form a positive electrode material layer 102 after baking, and then roll and cut to obtain the positive electrode 10. Among them, the positive electrode current collector 10 may include but is not limited to aluminum foil, aluminum alloy foil, a polymer film material coated with metal aluminum, or the aforementioned material with carbon coated on the surface.
[0030] The present application also provides a solid-state battery. Figure 2 , Figure 2 A schematic diagram of the structure of a solid-state battery provided in an embodiment of the present application. Figure 2 The solid-state battery 200 includes the above-mentioned positive electrode 10 of the embodiment of the present application, as well as the metal negative electrode 20, and the solid electrolyte membrane 30 located between the positive electrode 10 and the metal negative electrode 20. When the solid-state battery 200 is discharged for the first time, the metal negative electrode 20 can release active metal ions to the positive electrode 10, so that the positive electrode active material in the positive electrode 10 can subsequently continue to release / insert active ions.
[0031] In the embodiment of the present application, the metal negative electrode 20 may include a lithium metal negative electrode, a sodium metal negative electrode, a potassium metal negative electrode, a magnesium metal negative electrode, a zinc metal negative electrode or an aluminum metal negative electrode. Accordingly, the solid-state battery 200 may be a solid-state lithium ion battery, a solid-state sodium ion battery, a solid-state potassium ion battery, a solid-state magnesium ion battery, a solid-state zinc ion battery, or a solid-state aluminum ion battery. Among them, the active ions that the solid-state lithium ion battery relies on for energy storage are lithium ions (Li + ).
[0032] For solid-state lithium-ion batteries, the metal negative electrode 20 is a lithium metal negative electrode. Among them, the lithium metal negative electrode may include lithium single substance or lithium alloy. In the embodiment of the present application, the lithium single substance may include one or more of lithium sheets, lithium foil, and lithium powder. Among them, the lithium alloy may be one or more of lithium alloy sheets, lithium alloy foils, etc. Specifically, the lithium alloy may include at least one of lithium silicon alloy, lithium aluminum alloy, lithium tin alloy, and lithium indium alloy. Similarly, other metal negative electrodes may also be metal single substance negative electrodes or alloy negative electrodes.
[0033] In the embodiment of the present application, the solid electrolyte membrane 30 includes a second metal organic framework material (i.e., a second MOFs material, or a second porous coordination polymer), an electrolyte salt and a polymer matrix. In this case, the solid electrolyte membrane 30 is a composite solid electrolyte material, which has the function of conducting ions. Among them, the second MOFs material has a porous structure that can accommodate guest species, and its ion conductivity is relatively high. Introducing it into the solid electrolyte membrane 30 can make the ion conductivity of the solid electrolyte membrane 30 better, ensuring that during the charge and discharge process of the solid-state battery 200, the active ions can shuttle smoothly between the positive electrode 10 and the metal negative electrode 20.
[0034] Among them, in the solid electrolyte membrane 30, the electrolyte salt can provide the solid-state battery with active ions that can shuttle freely and play the role of transmitting ions inside the battery. The cations in the electrolyte salt can be selected according to the active ions that the solid-state battery 200 relies on for energy storage. For example, if the solid-state battery 200 is a solid-state lithium-ion battery, the electrolyte salt is a lithium salt; if the solid-state battery 200 is a solid-state sodium-ion battery, the electrolyte salt is a sodium salt. In the embodiment of the present application, the anions in the electrolyte salt include perchlorate (ClO4 - ), tetrafluoroborate (BF4 - ), hexafluorophosphate (PF6 - ), bis(trifluoromethylsulfonyl)imide (the ionic formula is N(SO2CF3)2 - , also known as TFSI-), bis(fluorosulfonyl)imide (with the ionic formula of N(SO2F)2 - , also known as FSI-) or more, but not limited to.
[0035] In some embodiments of the present application, the electrolyte salt used for the solid-state lithium-ion battery includes one or more of lithium perchlorate LiClO4, lithium tetrafluoroborate LiBF4, lithium hexafluorophosphate LiPF6, lithium bis(trifluoromethylsulfonyl)imide (abbreviated as LiTFSI, molecular formula is LiN(SO2CF3)2), and lithium bis(fluorosulfonyl)imide (abbreviated as LiFSI, molecular formula is LiN(SO2F)2). These lithium salts have good thermal stability and high ion conductivity.
[0036] In some embodiments of the present application, the second metal organic framework material includes one or more of aluminum-based MOFs, indium-based MOFs, zinc-based MOFs, and zirconium-based MOFs. That is, the metal ions in the second MOFs material include one or more of aluminum ions, indium ions, zinc ions, and zirconium ions. These ions have high coordination ability. In addition to being able to coordinate with the organic ligands that constitute the second MOFs, they also have open sites that can be combined with anions in the electrolyte salt, thereby improving the active ions (such as Li + ) The number of migration increases and the ion conductivity increases, which is beneficial to the improvement of the electrochemical reaction kinetics of the battery, especially the fast charging performance. In some embodiments, the metal ions in the second MOFs material are indium ions or zinc ions. The ion conductivity of the second MOFs material using these two ions as the central metal ions is higher.
[0037] In an embodiment of the present application, the organic ligand in the second MOFs material may include at least one of benzene-1,3,5-tricarboxylic acid (BTC, also known as benzene-1,3,5-tricarboxylic acid), benzene-1,4-dicarboxylic acid (BDC), azobenzene-4,4'-dicarboxylic acid (ADC), and isonicotinic acid (IN).
[0038] In some embodiments of the present application, aluminum-based MOFs may be MIL-100 (Al), and its organic ligand is BTC. Indium-based MOFs may be MIL-68 (In). Zinc-based MOFs may be zeolitic imidazolate framework materials (ZIF), which are a type of MOFs materials self-assembled by tetrahedral coordination of nitrogen-containing organic ligands (such as imidazole) and divalent zinc ions. Zirconium-based MOFs may be Zr6O4(OH)4(BDC) 12 Among them, the names and corresponding structures of the above MOFs materials can be found in the Cambridge Structural Database (CSD) or other public literature.
[0039] In the above-mentioned solid electrolyte membrane 30, the polymer matrix can bond the second MOFs material and the electrolyte salt together to form a composite solid electrolyte material, and ensure that the cohesion of the solid electrolyte membrane 30 is high and the structure is stable. In addition, the polymer matrix should also have good ion conductivity. In the embodiment of the present application, the polymer matrix includes one or more of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene oxide PEO, polypropylene oxide PPO, polyvinylidene fluoride PVDF, polytetrafluoroethylene PTFE, polyacrylonitrile (PAN), and polyacrylate. These polymer matrices have high ion conductivity and good adhesion.
[0040] In the embodiment of the present application, the solid electrolyte membrane 30 includes the following components in percentage by weight: 70-75wt% of the second metal organic framework material, 10-15wt% of the electrolyte salt, and 15-20wt% of the polymer matrix. The solid electrolyte membrane 30 includes an appropriate amount of the second MOFs material, the electrolyte salt and the polymer matrix, which can ensure that the solid electrolyte membrane 30 has a stable structure, a high ion conductivity and an ion migration number.
[0041] In the present application, the solid-state battery 200 can be assembled by the following method: in a glove box filled with inert gas, the positive electrode 10, the solid electrolyte membrane 30, and the metal negative electrode 20 are stacked in order to form a battery cell; the battery cell is packaged to obtain a solid-state battery. The solid-state battery is subjected to electrochemical performance testing after formation and capacity separation.
[0042] The solid-state battery 200 includes the positive electrode 10 of the embodiment of the present application. The solid-state battery 200 has good rate performance, good cycle performance, high safety, and a high discharge / charge specific capacity, and thus a high battery energy density.
[0043] The embodiment of the present application also provides a device, which includes the above-mentioned solid-state battery of the embodiment of the present application. Among them, the device can be an electric vehicle (such as a car, a motorcycle, a bicycle, etc.), an electric toy, a 3C product (such as a mobile phone, a laptop, a tablet computer, a pen-input computer, an e-book player, a wearable device, etc.) and other electrical equipment; it can also be an energy storage system. Among them, the energy storage system can include a plurality of the above-mentioned solid-state batteries, and a battery management system. The energy storage system can also supply power to electrical equipment. Among them, the electrical equipment powered by the above-mentioned solid-state battery has a fast charging speed and a long operating time.
[0044] The embodiments of the present application are further described below with reference to a plurality of embodiments.
[0045] Example 1 - Preparation of positive electrode for solid-state battery
[0046] The organic ligand 1,4-benzoquinone shown in the above-mentioned label 9 is dispersed in the solvent methanol to obtain a ligand solution; a metal copper salt is dissolved in water to obtain a metal salt solution; the two solutions are mixed, and the molar equivalent ratio of the organic ligand to the metal ion is controlled to be 1:0.5 to obtain a mixed solution; the mixed solution is dried to obtain Cu-MOFs (CuC6O2H2) material powder, which can be used as a positive electrode active material.
[0047] The first MOFs material powder and the conductive agent (specifically: conductive carbon black) are blended in a mixer, and the resulting mixed dry material is dispersed in NMP containing a binder (specifically: polyvinylidene fluoride, PVDF), and then fully stirred using a vacuum planetary mixer to obtain a uniformly mixed positive electrode slurry; wherein, in the positive electrode slurry, the mass ratio of the first MOFs material, the conductive agent, and the binder is 8:1:1. The positive electrode slurry is coated on a carbon-coated aluminum foil with a thickness of 17μm using a coating machine, and the coating thickness is 150μm, and then dried in a vacuum oven at 120°C for 24h, and then the dried electrode is roller pressed (the compaction is controlled at 2.5mg / cm 3 ) and cut to obtain the positive electrode sheet, recorded as P1.
[0048] Example 2
[0049] The difference between this embodiment and Example 1 is that the type of organic ligand is changed. Specifically, the ligand with number 9 is replaced by the ligand with number 1, and the rest of the preparation is the same as that of Example 1. A positive electrode sheet is obtained, which is recorded as P2.
[0050] Example 3
[0051] The difference between this embodiment and Example 1 is that the type of organic ligand is changed. Specifically, the ligand with number 2 is used to replace the ligand with number 9, and the rest of the preparation is the same as that of Example 1. A positive electrode sheet is obtained, which is recorded as P3.
[0052] Example 4
[0053] The difference between this embodiment and Example 1 is that the type of organic ligand is changed. Specifically, the ligand with number 9 is replaced by the ligand with number 3, and the rest of the preparation is the same as that of Example 1. A positive electrode sheet is obtained, which is recorded as P4.
[0054] Example 5
[0055] The difference between this embodiment and Example 1 is that the type of organic ligand is changed. Specifically, the ligand with number 4 is used to replace the ligand with number 9, and the rest of the preparation is the same as that of Example 1. A positive electrode sheet is obtained, which is recorded as P5.
[0056] Example 6
[0057] The difference between this embodiment and Example 1 is that the type of organic ligand is changed. Specifically, the ligand with number 5 is used to replace the ligand with number 9, and the rest of the preparation is the same as that of Example 1. A positive electrode sheet is obtained, which is recorded as P6.
[0058] Example 7
[0059] The difference between this embodiment and Example 1 is that the type of organic ligand is changed. Specifically, the ligand with number 6 is used to replace the ligand with number 9, and the rest of the preparation is the same as that of Example 1. A positive electrode sheet is obtained, which is recorded as P7.
[0060] Example 8
[0061] The difference between this embodiment and Example 1 is that the type of organic ligand is changed. Specifically, the ligand with number 7 is used to replace the ligand with number 9, and the rest of the preparation is the same as that of Example 1. A positive electrode sheet is obtained, which is recorded as P8.
[0062] Example 9
[0063] The difference between this embodiment and Example 1 is that the type of organic ligand is changed. Specifically, the ligand with number 8 is used to replace the ligand with number 9, and the rest of the preparation is the same as that of Example 1. A positive electrode sheet is obtained, which is recorded as P9.
[0064] Example 10
[0065] The difference between this embodiment and Example 1 is that the type of organic ligand is changed. Specifically, the ligand with number 9 is replaced by the ligand with number 10, and the rest of the preparation is the same as that of Example 1. A positive electrode sheet is obtained, which is recorded as P10.
[0066] Embodiment 11
[0067] The difference between this embodiment and Example 1 is that the type of organic ligand is changed. Specifically, the ligand with number 9 is replaced by the ligand with number 11, and the rest of the preparation is the same as that of Example 1. A positive electrode sheet is obtained, which is recorded as P11.
[0068] Example 12
[0069] The difference between this embodiment and Example 1 is that the type of organic ligand is changed. Specifically, the ligand with number 9 is replaced by the ligand with number 12, and the rest of the preparation is the same as that of Example 1. A positive electrode sheet is obtained, which is recorded as P12.
[0070] Comparative Example 1
[0071] The difference between this embodiment and Example 1 is that the type of organic ligand is changed. Specifically, the ligand No. 9 is replaced by 2,5-dihydroxyterephthalic acid, the molar ratio of metal to 2,5-dihydroxyterephthalic acid is about 2:1, and the solvent used is generally DMF:EtOH, the volume ratio is 1:1, and a mixed solution is obtained; the mixed solution is dried to obtain MOF-74 (Cu) material powder. A positive electrode sheet is obtained, which is recorded as DP1.
[0072] Comparative Example 2
[0073] The difference between this embodiment and Example 1 is that the type of positive electrode is changed. Specifically, lithium iron phosphate is used to replace the Cu-MOFs used in Example 1, and the rest of the preparation is the same as that in Example 1. A positive electrode sheet is obtained, which is recorded as DP2.
[0074] Preparation Example 2.1 of Solid Electrolyte Membrane:
[0075] 1) Preparation of the second MOFs material: dissolve terephthalic acid (1 mol) in 100 mL of DMF, then add 100 mL of an aqueous solution containing In(NO3)2 (0.5 mol), mix well and transfer to a 300 mL glass bottle, seal and stir for 24 hours, and solid precipitates after natural sedimentation. Filter the stirred reaction mass to obtain a solid, and wash the solid three times with water and ethanol and then dry it to obtain an indium-based MOFs sample ((In)MOF).
[0076] Next, the synthesized sample is added to a low-boiling point solvent, methanol, and placed in an oven at 50-60°C for constant temperature heating. Fresh methanol is replaced several times a day to exchange out the high-boiling point solvent in the sample. The exchange is repeated for 3-5 days, and then the sample is dried in a vacuum oven at 130-160°C for 12-24 hours to obtain an activated dry sample.
[0077] 2) The activated dry sample is placed in a DMF dispersion of lithium salt LiTFSI, and placed in an oven at 50-60°C for constant temperature heating. The DMF dispersion of LiTFSI is replaced once a day to exchange the counter cations in MOFs and introduce lithium salts into the pores of MOFs. After 5-7 days of exchange, the sample is dried in a vacuum oven at 50-60°C for 12-24 hours to obtain a sample after lithium ion exchange, which is recorded as Li@MOFs.
[0078] 3) The Li@MOFs sample was dispersed in a solvent DMF (N,N-dimethylformamide), stirred at room temperature for 15-30 minutes, and then PVDF-HFP was added. After stirring at room temperature for 30-60 minutes, the lithium salt LiTFSI was added. After constant temperature stirring at 65°C for 12 hours, the resulting mixture was injected into a clean culture dish, left to stand at room temperature for 24 hours, and then dried under vacuum at 60-80°C for 12-24 hours to obtain a solid electrolyte membrane (i.e., Li@MOFs / PVDF-HFP / LiTFSI). After that, the obtained solid electrolyte membrane was cut into a disc with a diameter of 16 mm, and transferred to a glove box filled with argon gas, immersed in a propylene carbonate solution of LiTFSI with a concentration of 0.1M for 24 hours, and then taken out and dried at room temperature for 12 hours to obtain a solid electrolyte membrane that can be used for battery assembly, which is recorded as S1.
[0079] Other solid electrolyte membranes S2 to S5 were prepared by following the method of the above-mentioned preparation example 2.1. Among them, the difference between the solid electrolyte membrane S2 and S1 is that the lithium salt LiTFSI used is replaced by LiPF6; the difference between the solid electrolyte membrane S3 and S1 is that the lithium salt LiTFSI used is replaced by LiClO4; the difference between the solid electrolyte membrane S4 and S1 is that the lithium salt LiTFSI used is replaced by LiBF4; the difference between the solid electrolyte membrane S5 and S1 is that the lithium salt LiTFSI used is replaced by LiFSI.
[0080] Performance test of solid electrolyte membrane:
[0081] Using stainless steel sheets (SS) as blocking electrodes, the above solid electrolyte membranes S1-S5 were assembled into SS / solid electrolyte membrane / SS batteries, and impedance tests were performed at a temperature range of -15 to 100°C.
[0082] The calculation formula of ionic conductivity σ is: σ = L / (R×S), where L represents the thickness of the solid electrolyte membrane sample (cm), R represents the impedance of the sample (Ω), and S represents the area of the sample (cm 2 ).
[0083] In addition, the Arrenius relationship between ionic conductivity σ and temperature T is: σT = A × exp(-E a / k B T)(2), where A is the pre-exponential parameter; T is the absolute temperature; E a is the activation energy of ionic conduction; k B is the Boltzmann constant, approximately 1.381×10 -23 J / K. The above formula (2) is transformed into: Therefore, log(σT) and 1000 / T satisfy a linear relationship. With log(σT) as the Y-axis and 1000 / T as the X-axis, the slope of the straight line is obtained by fitting: Ea / k B , calculate the activation energy E of the solid electrolyte a , and then calculate its ionic conductivity σ, and the results are summarized in the following Table 1.
[0084] In addition, the AC impedance method is combined with the chronoamperometry to test the ion migration number of the solid electrolyte membrane. Specifically, the above-mentioned solid electrolyte membranes S1-S5 are respectively assembled into Li / solid electrolyte membrane / Li symmetrical batteries, and DC polarization tests are performed using an electrochemical workstation, wherein DC polarization is achieved by applying a constant voltage of 10mV for 12h. The AC impedance before and after DC polarization is tested using an electrochemical workstation, and the frequency is set to 1MHz~0.1Hz. Among them, the lithium ion migration number of the electrolyte membrane is calculated as follows: t Li+ =Iss (Δv-I0R0) / I0(Δv-I ss R ss );
[0085] Where I0 represents the initial current (A); I SS represents the steady-state current (A); R0 represents the impedance of the electrolyte membrane before DC polarization (Ω); R SS represents the impedance of the electrolyte membrane after DC polarization (Ω); Δv represents the applied DC polarization voltage (V). The calculation results of the lithium ion transference number are summarized in Table 1 below.
[0086] Table 1
[0087] Group <![CDATA[Ionic conductivity (S·cm –1 )]]> Ion migration number S1 <![CDATA[9.1×10 –4 ]]> 0.78 S2 <![CDATA[8.9×10 –4 ]]> 0.74 S3 <![CDATA[8.6×10 –4 ]]> 0.76 S4 <![CDATA[9.0×10 –4 ]]> 0.77 S5 <![CDATA[9.1×10 –4 ]]> 0.78
[0088] It can be seen from Table 1 that the solid electrolyte membrane provided by the present application has a higher ion conductivity and a larger ion migration number.
[0089] Assembly and testing of solid-state batteries:
[0090] The assembly of the solid-state lithium-ion battery includes: in a glove box filled with argon, stacking the positive electrode sheets P1-P12 prepared in Examples 1-12, the solid electrolyte membrane S1 prepared above, and the metal lithium negative electrode (specifically a lithium sheet) in sequence, and encapsulating them in a battery shell to obtain solid-state lithium-ion batteries B1-B12. In addition, the positive electrode sheet P1 prepared in Example 1, the solid electrolyte membrane S2-S5 prepared above, and the metal lithium negative electrode (specifically a lithium sheet) are stacked in sequence and encapsulated in a battery shell to obtain solid-state lithium-ion batteries B13-B16. The positive electrode sheets DP1-DP2 prepared in Comparative Examples 1-2, the prepared solid electrolyte membrane S1, and the metal lithium negative electrode (specifically a lithium sheet) are stacked in sequence and encapsulated in a battery shell to obtain solid-state lithium-ion batteries DB1-DB2.
[0091] After the formation and capacity division of the above solid-state lithium-ion batteries at room temperature, they were charged and discharged for 3 cycles with a small current of 0.33C to achieve the purpose of activation, so as to conduct subsequent electrochemical performance tests, and record the charging capacity C0 of the third charge. Then, the activated battery was charged to an upper voltage of 3.8V at different rates (1C, 5C), and discharged to a lower voltage of 2.0V at 0.33C. The ratio of the charging capacity of the battery at different charging rates to the above C0 was used as the charging ratio at the corresponding rate. Each solid-state lithium-ion battery was also subjected to a room temperature cycle performance test, with a charge and discharge rate of 0.33C and a voltage range of 2.0-3.8V. The discharge capacity retention rate after 100 cycles and the battery specific capacity of the first cycle discharge were recorded. The relevant results are summarized in Table 2 below.
[0092] Table 2 Electrochemical performance test results of solid-state batteries
[0093]
[0094] From the comparison of solid-state batteries B1-B12 and DB1-DB2 in Table 2, it can be seen that the solid-state lithium-ion batteries B1-B12 assembled using the positive electrodes of the embodiments of the present application have a first-cycle discharge capacity and a charging ratio at different charging rates that are significantly higher than the currently commercialized lithium iron phosphate battery (DB2), and the cycle capacity retention rate is also excellent. The battery performance of the above-mentioned solid-state batteries B1-B12 is also better than that of the battery DB1 of comparative example 1 in which the ligand of the positive electrode MOFs material does not contain a carbonyl group. The solid-state batteries B13-B16 of the present application, in which the positive electrode remains unchanged and the solid-state electrolyte membrane is changed, also have similar effects to the above-mentioned solid-state batteries B1-B12.
[0095] Among them, the organic ligands in the positive electrode MOFs of the batteries B1, B10, B11, and B12 of the embodiments of the present application are the aforementioned compounds 9-12, which have conjugated large π bonds in their molecules. The positive electrode MOFs using them have higher conductivity, and the battery's rate performance and cycle stability are excellent, which are better than batteries B2 to B9; in addition, because the molecular weight of the organic ligands in the positive electrode MOFs of B11 and B12 is higher, the discharge specific capacity of batteries B11 and B12 will be lower than that of batteries B1 and B10.
[0096] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A positive electrode for a solid-state battery, characterized in that: The positive electrode includes a positive electrode current collector and a positive electrode material layer arranged on the surface of at least one side of the positive electrode current collector, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes a metal organic framework material, wherein the organic ligand of the metal organic framework material includes at least one carbon ring with 4-6 carbon atoms, and at least one of the carbon rings has at least one carbonyl group embedded therein.
2. The positive electrode according to claim 1, characterized in that The organic ligand contains 1 to 4 carbonyl groups.
3. The positive electrode according to claim 1 or 2, characterized in that The organic ligand includes one or more of the following compounds:
4. The positive electrode according to any one of claims 1 to 3, characterized in that The metal ions of the metal organic framework material are variable valence transition metal ions.
5. The positive electrode according to claim 4, characterized in that The variable-valence transition metal ions include one or more of copper ions, iron ions, and manganese ions.
6. The positive electrode according to any one of claims 1 to 5, characterized in that The positive electrode material layer further includes a binder and a conductive agent.
7. The positive electrode according to claim 6, characterized in that The positive electrode material layer includes the following components in percentage by mass: 80%-99% of the positive electrode active material, 0.5%-10% of the binder, and 0.5%-10% of the conductive agent.
8. The positive electrode according to any one of claims 1 to 7, characterized in that The mass percentage of the metal organic framework material in the positive electrode material layer is greater than or equal to 80% and less than or equal to 99%.
9. A solid-state battery, characterized in that: It comprises a positive electrode as described in any one of claims 1 to 8, a metal negative electrode, and a solid electrolyte membrane located between the positive electrode and the metal negative electrode.
10. The solid-state battery according to claim 9, characterized in that: The solid electrolyte membrane includes a second metal organic framework material, an electrolyte salt and a polymer matrix; wherein the second metal organic framework material includes one or more of an aluminum-based metal organic framework material, an indium-based metal organic framework material, a zinc-based metal organic framework material, and a zirconium-based metal organic framework material.
11. The solid-state battery according to claim 10, characterized in that: The anions in the electrolyte salt include ClO4 - 、BF4 - PF6 - , TFSI- or FSI-.
12. The solid-state battery according to claim 10 or 11, characterized in that: The electrolyte salt is a lithium salt.
13. The solid-state battery according to any one of claims 10 to 12, characterized in that: The polymer matrix includes one or more of polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, polypropylene oxide, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, and polyacrylate.
14. The solid-state battery according to any one of claims 10 to 13, characterized in that: The solid electrolyte membrane comprises the following components in percentage by mass: 70-75% of the second metal organic framework material, 10-15% of the electrolyte salt, and 15-20% of the polymer matrix.
15. The solid-state battery according to any one of claims 9 to 14, characterized in that: The metal negative electrode is a lithium metal negative electrode; optionally, the lithium metal negative electrode includes one or more of a lithium sheet, a lithium foil, a lithium powder, and a lithium alloy.
16. A device comprising the solid-state battery according to any one of claims 9 to 15, wherein the device comprises an electrical device or an energy storage system.